Correcting Susceptibility-Induced Distortion in Diffusion-Weighted MRI using Constrained Nonrigid Registration - Bhushan, Chitresh (Signal Inf Process Assoc Annu Summit Conf APSIPA Asia Pac, 2012)
Echo Planar Imaging (EPI) is the standard pulse sequence used in fast diffusion-weighted magnetic resonance imaging (MRI), but is sensitive to susceptibility-induced inhomogeneities in the main B(0) magnetic field. In diffusion MRI of the human head, this leads to geometric distortion of the brain in reconstructed diffusion images, and a lack of correspondence with undistorted high-resolution MRI scans that are used to define the subject anatomy. In this study, we have tested an approach to estimate and correct this distortion of using a non-linear registration framework based on mutual-information. We use the commonly acquired anatomical image as the registration-template and constrain the registration using spatial regularization and physics-based information about the characteristics of the distortion, but without requiring any additional data collection. Results are shown for simulated and experimental data.